Urgensi Karya Ilmiah dalam Pengembangan Pengetahuan Ilmiah dan Etika Keilmuan di Perguruan Tinggi - Sartika Sartika; Efendi Efendi; Muhammad Zalnur (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Scientific writing plays an important role in developing knowledge and shaping the intellectual character of students. Through academic writing, students not only learn to organize ideas systematically but are also trained to think critically, analytically, and reflectively. This study employs a literature review method to examine the concepts, processes, and originality of scientific work based on academic theories and established scholarly standards. The findings indicate that writing scientific papers is not merely an academic requirement but also a reflection of logical, objective, and ethical thinking. A high-quality scientific work must demonstrate originality, intellectual honesty, and the proper application of scientific methods—from problem formulation and data collection to analysis and conclusion. In addition, scientific writing should contribute to the development of knowledge and offer solutions to current issues in society. Therefore, higher education institutions need to strengthen students’ scientific literacy, academic writing skills, and understanding of research ethics. These efforts are essential for fostering an academic culture that upholds integrity, encourages innovation, and prepares young scholars to become responsible and competitive individuals.